Functional neuroimaging: a physiological perspective - Lin, Ai-Ling; Gao, Jia-Hong; Duong, Timonthy Q.; Fox, Peter T. (Frontiers in Neuroenergetics, 2010)
Metabolic physiology and functional neuroimaging have played important and complementary roles over the past two decades. In particular, investigations of the mechanisms underlying functional neuroimaging signals have produced fundamental new insights into hemodynamic and metabolic regulation. However, controversies were also raised as regards the metabolic pathways (oxidative vs. non-oxidative) for meeting the energy demand and driving the increases in cerebral blood flow (CBF) during brain activation. In a recent study, with the concurrent functional MRI-MRS measurements, we found that task-evoked energy demand was predominately met through oxidative metabolism (approximately 98%), despite a small increase in cerebral metabolic rate of oxygen (12–17%). In addition, the task-induced increases in CBF were most likely mediated by anaerobic glycolysis rather than oxygen demand. These observations and others from functional neuroimaging support the activation-induced neuron-astrocyte interactions portrayed by the astrocyte-neuron lactate shuttle model. The concurrent developments of neuroimaging methods and metabolic physiology will also pave the way for the future investigation of cerebral hemodynamics and metabolism in disease states.